Donne's Anniversaries and the Poetry of Praise : The Creation of a Symbolic Mode - Lewalski, Barbara Kiefer, 1931-2018 (Book collections on Project MUSE., 1973)
In his occasional poetry, and especially in his two elegaic Anniversary poems, Donne created a special symbolic mode in seventeenth-century poetry of praise and compliment. Barbara Kiefer Lewalski's reading of the Anniversary poems recognizes them as complex mixed-genre works which weld together formal, thematic, and structural elements from the occasional poem of praise, the funeral elegy, the funeral sermon, the hymn, the anatomy, and the Protestant meditation. Focusing especially on theme and structure, her reading demonstrates the coherent symbolic method and meaning of these poems and a.